Dopant transfer from poly-si thin films to c-Si: An alternative technique for device processing. (February 2016) - Ricardo, L.; Amaral, A.; Nunes de Carvalho, C.; Lavareda, G.
Abstract: An alternative technique for production of devices which uses both silicon crystalline wafers (p-type) and heavy doped amorphous silicon thin films (n-type) is reported. The amorphous silicon acts as a finite source of dopant and is deposited (at low temperature, 70 °C) by plasma enhanced chemical vapor deposition on silicon wafers. Afterwards, the process of dopant diffusion into the crystalline silicon occurs in a diffusion furnace at 1000 °C for 2 h, to create p–n junctions. Using SIMS analyses, a dopant (P) transfer into c-Si of about 30% is verified and 87% of the dopant transferred is electrically active. Consequently, n-MOSFET devices are produced using a gate oxide thermally grown at the same diffusion temperature for one hour. The preliminary results of the MOSFET (channel length and width of 0.5 and 5 mm, respectively) show a depletion behavior with a threshold voltage, Vth =−8.2 V and afield-effect mobility, µFE =187.8 cm 2 /(Vs).